Incidence of phlebitis in patients with peripheral catheter in a health care institution in Manizales (Colombia) - Campiño-Valderrama, Sandra Milena; Yaquibe-Murcia, Jhon Fredy; Aristizábal-Cardona, Sandra Milena; Henao-Lasso, Estefany; Ramírez-Botero, Melissa; Vinasco-Rodriguez, Maria Alejandra (Universidad y Salud, 2022)
Introduction: Nursing care in clinical areas requires knowledge, skills, and experience. Treatment of a hospitalized person usually requires venous access, which carries frequently reported complications such as phlebitis and infiltrations. Objective: To determine the incidence of phlebitis in patients with short peripheral catheter according to its grade and various factors involved in its appearance. Materials and methods: Quantitative, prospective, observational, and documentary study carried out between October 2018 and February 2019. Results: An incidence rate of phlebitis of 18.5% was observed. Phlebitis was reported in 157 out of 849 children with peripheral venous catheter. Grade I, II, III, and IV phlebitis was documented in 52.2%, 29.9%, 15.3%, and 2.5%. respectively. 78% of the children showed adequate weight and height for their age group. These cases of phlebitis were related to preventive catheter and associated with the use of medications such as cephalothin and dipyrone. In the case of grade I phlebitis, it was more frequent in childhood and adolescent populations. Conclusions: The identification of phlebitis, its grades, and its correlation with sociodemographic variables is necessary to establish health care actions and promote strategies in order to improve care and achieve high quality standards.